Transformacija visokog obrazvanja - nemoguća misija ili razvojna šansa? / Higher Education Transformation - Mission Impossible or Chance for Development? (Pregled: časopis za društvena pitanja / Periodical for social issues, 2025)
The University of Sarajevo and the Sarajevo Cantonal Government’s Ministry of Science, Higher Education and Youth organized the Consultation “The Future of Education: Higher Education for Sustainable Development 2030” both as a response to global trends in the societal transformation and a response to the Bosnian-Herzegovinian society’s needs for better education as the foundation of the necessary progress. The key challenge for our society, and therefore the University of Sarajevo, is the way we observe and organize learning and education, especially within the context of rapidly changing technological, economic and social development.